Achieving Sustainable Ecological Justice through Land Transfer Regulation in Indonesia - Ayik Christina Efata; Retno Mawarini; Widyorini Indriasti Wardani; Mohammad Ishaque Husain (Contrarius Indonesia, 2026)
This study examines the legal implications of land conversion as a process that alters land use either partially or entirely and consequently affects environmental sustainability and the productive capacity of land resources. The increasing transformation of agricultural land into non-agricultural uses reduces the availability of productive farmland and generates serious challenges for government authorities in maintaining food security and ensuring sustainable land governance. Economic growth, urban expansion, and development policies frequently encourage the conversion of agricultural land and thereby intensify pressure on the availability of land that supports long term agricultural production. These conditions require a regulatory framework that is capable of balancing development interests with the protection of agricultural land resources. This research analyzes the regulatory framework governing the conversion of sustainable food agricultural land into non-agricultural uses, identifies the factors that create the absence of legal certainty in its implementation, and formulates a reconstruction of regulatory policies that can strengthen legal certainty in land governance. The study applies a normative juridical research method supported by empirical data and uses statutory, conceptual, and comparative approaches to examine the issue systematically. The analysis demonstrates that first, the legal system has integrated land conversion regulation within the broader framework of sustainable agricultural land protection and spatial planning governance. Second, implementation has not produced adequate legal certainty because uncontrolled land conversion continues to occur, land use practices frequently diverge from spatial planning policies, regulatory substance remains weak, law enforcement operates ineffectively, and institutional coordination remains limited. Third, strengthening legal certainty requires regulatory reconstruction through harmonization of regulatory instruments, improvement of mapping mechanisms supported by field verification, and stronger coordination between central and regional governments.